Giuseppe de Lorenzo and his "Buddhist" reading of Shakespeare = Giuseppe de Lorenzo i jego "buddyjska" interpretacja Szekspira - Salvati, Antonio (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Giuseppe De Lorenzo (1871-1957) was a geologist, a translator of Buddhist texts and Schopenhauer, a great reader of Shakespeare and senator of the Italian Kingdom since 1913. His multifaceted figure has been discussed and criticised over the years, but it keeps arousing great interest both in respect to the history of European culture in the early twentieth century and the history of Buddhism in Italy. "Shakespeare e il dolore del mondo" (published in 1921), can be considered De Lorenzo`s first specific attempt to read into the works of major western poets and philosophers an idea of pain that is actualized as a constant dimension.
Keywords: Shakespeare, William (dramaturg, poeta; 1564-1616); Lorenzo, Giuseppe de (1871-1957); History of Religions; English Literature; Buddhism; pain; suffering; religia- historia; literatura angielska; Buddyzm; ból; cierpienie